PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN PENGELOLAAN KEUANGAN DALAM MENINGKATKAN KINERJA UMKM DI KABUPATEN SLEMAN - Widiawati, Ani; Wulandari, Ika (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
The lack of understanding of financial literacy, financial inclusion, and financial management among MSME players makes it difficult for them to prepare financial reports, which can hinder the performance of MSMEs. This research aims to determine the influence of financial literacy, financial inclusion, and financial management on the MSMEs' performance. This research is a type of quantitative research. Sleman Regency is the location for this research. The population considered was 90,581 MSME actors. By calculating using the Slovin formula and getting sample results from 100 respondents, The sampling technique uses probability sampling. This research uses primary data and a Google Form questionnaire to collect the data. Data analysis in this research used the SPSS version 26 program. The data analysis methods used were instrument data testing, descriptive statistical analysis, classical hypothesis testing, multiple linear regression testing, and hypothesis testing. Based on the research results, financial literacy has a positive and significant effect on MSME performance, financial inclusion has a positive and significant effect on MSME performance, and financial management does not affect MSME performance.